ACUTE TOXICITY OF PESTICIDES IN THE FRESH WATER FISH BARBUS STIGMA : HISTOPATHOLOGY OF THE STOMACH - KHILLARE, Y. K.; WAGH, S. B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Toxicity tests of Endosulfan, Malathion and Sevin were carried out using fish, B. Stigma, exposed for 96 h. Histopathological changes in the stomach were studied. Several changes were found in the texture of the digestive tract, epithelial cells and mucosal layer; atrophy of the mucosa was present. Endosulfan induced more changes than Malathion. It may be noted that rupture of the cells and deformation in texture of the tissue may affect the functional activity of the digestive enzymes. This may interfere with the digestion, resulting in reduced appetite and growth rate.